Penyelamatan, Rehabilitasi, dan Pelepasliaran Penyu di Pusat Pendidikan dan Konservasi Penyu Binaan CSR Pertamina Patra Niaga Fuel Terminal Sanggaran, Bali: Menjaga Keseimbangan Ekosistem Laut dan Meningkatkan Kesadaran Masyarakat - Parawangsa, I Nyoman Y.; Lesmana, I Wayan Indera; Sukanta, I Made; Semarariana, I Wayan Yustisia; Utami, Dhita Hardiyanti (IAI Nasional Laa Roiba Bogor, 2025)
Turtles are one of the living fossils whose population conditions are currently in a worrying state. Several factors that threaten the turtle population include illegal trade, water pollution, global climate change, and fishing activities. TCEC is a non-governmental institution that has a turtle rescue program as a conservation effort. TCEC has rescued turtles from various threats. The purpose of this study was to determine the types of threats, types of threatened turtles, the number of turtles rescued and the appropriate medical actions in efforts to rescue and rehabilitate turtles carried out by TCEC. Turtle rescue data was inventoried from 2015 - April 2025. Data analysis carried out included the number, types of turtles rescued and the types of threats for each year. This data can provide an overview of the background and context that are important for understanding cases of turtle rescue from various threats encountered by TCEC. The number of turtles successfully rescued by TCEC was 287. The number of turtles rescued from the threat of bycatch was 4 individuals, stranded as many as 43 individuals and from illegal trade as many as 238 individuals. Each rescued turtle will receive medical treatment appropriate to the turtle's condition from a veterinarian and after its condition has recovered, it will be released into its habitat. Illegal trade is still a very big threat to the turtle population. These results indicate that turtle conservation stakeholders must continue to run campaigns related to the eradication of turtle trade and educate the public to raise awareness to stop consuming turtles.